Pengalaman Pasien Diabetes Melitus Tipe 2 dalam Melakukan Tindakan Pencegahan Terjadinya Luka pada Kaki - Nur Afni Wulandari; Agung Waluyo; Diana Irawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to gain an in-depth understanding of the meaning and significance of the experience of type 2 diabetes mellitus patients in taking preventive measures for injury at PERSADIA Islamic Hospital Jakarta Pondok Kopi. This study uses a qualitative design and data collection is done by in-depth interview techniques. The results obtained were four) themes produced, namely the picture of maintaining diet, diverse blood sugar control activities, the challenges of therapeutic adherence and the ability to properly care for the feet. Conclusion, the experience of type 2 diabetes mellitus patients in preventing injuries, should adhere to the treatment and maintain the food according to diet so that blood sugar levels remain stable. Another thing to note is, the active role of health workers in providing education about proper foot care. Keywords: Type 2 Diabetes Mellitus, Prevention of Wound Occurrence